An intercomparison of satellite-based daily evapotranspiration estimates under different eco-climatic regions in South Africa - Majozi, Nobuhle P.; Mannaerts, Chris M.; Ramoelo, Abel; Mathieu, Renaud; Mudau, Azwitamisi E.; Verhoef, Wouter (Remote Sensing, 2017)
Knowledge of evapotranspiration (ET) is essential for enhancing our understanding of the hydrological cycle, as well as for managing water resources, particularly in semi-arid regions. Remote sensing offers a comprehensive means of monitoring this phenomenon at different spatial and temporal intervals. Currently, several satellite methods exist and are used to assess ET at various spatial and temporal resolutions with various degrees of accuracy and precision. This research investigated the performance of three satellite-based ET algorithms and two global products, namely landsurfacetemperature/vegetationindex(TsVI),Penman–Monteith(PM),andtheMeteosatSecond Generation ET (MET) and the Global Land-surface Evaporation: the Amsterdam Methodology (GLEAM) global products, in two eco-regions of South Africa. Daily ET derived from the eddy covariance system from Skukuza, a sub-tropical, savanna biome, and large aperture boundary layer scintillometer system in Elandsberg, a Mediterranean, fynbos biome, during the dry and wet seasons, were used to evaluate the models. Low coefﬁcients of determination (R2) of between 0 and 0.45 were recorded on both sites, during both seasons. Although PM performed best during periods of high ET at both sites, results show it was outperformed by other models during low ET times. TsVI and MET weresimilarlyaccurateinthedryseasoninSkukuza,asGLEAMwasthemostaccurateinElandsberg during the wet season. The conclusion is that none of the models performed well, as shown by low R2 and high errors in all the models. In essence, our results conclude that further investigation of the PM model is possible to improve its estimation of low ET measurements.
Journal article published in the Journal of Remote Sensing 2017, 9, 307
Keywords: Latent heat ﬂux; Evapotranspiration; Remote sensing; Eddy covariance; Large aperture boundary layer scintillometer; Evapotranspiration -- South Africa; Remote sensing -- South Africa; Climatic changes -- South Africa; Evaporation, Latent heat of